Internet of Things: A survey of enabling technologies in healthcare and its applications - Dhanvijay, Mrinai M.; Patil, Shailaja C. (Computer networks (Amsterdam, Netherlands : 1999), 2019)
Internet of Things (IoT) on the Wireless Body Area Network (WBAN) for healthcare applications is an operative scenario for IoT devices that has gained attention from vast research fields in recent years. The IoT connects all subjects and the healthcare system seamlessly. This paper describes the WBAN based IoT healthcare system and reviews the state-of-the-art of the network architecture topology and applications in the IoT based healthcare solutions. Moreover, this paper analyzes the security and the privacy features consisting of privacy, authentication, energy, power, resource management, Quality of Services and the real-time wireless health monitoring that are quite problematic in many IoT healthcare architectures. Because, system architecture is not well-defined, data restriction and its integrity preservation is still a challenge. At present 90% of the information available is acquired in the recent two years. This survey mainly aims at analyzing healthcare purpose which is based on digital healthcare system. Further, it reports many IoT and the e-healthcare policies and systems that decide how to ease all bearable development. Thus, the overall system provides large possibilities for future research based on IoT healthcare system. Finally, research gaps are reviewed and the possible future aspects have been discussed.